Fifth formers of St Clare's - Blyton, Enid. (b, 2013)
The twins have made it to the fifth form, but are not too old for tricks and escapades, jokes and excitement. Especially amusing is French girl Antoinette who, like her sister Claudine, doesn't always understand the ways of St Clare's. But the new term brings new responsibilities and challenges - the girls have their own studies now, yet again, a new head girl is to be appointed and then there are three new girls who prove very unpopular. There's never a dull moment at St. Clare's.
Keywords: Saint Clare's (Imaginary organization) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Friendship -- Juvenile fiction